Detecting Voluntary Gait Initiation/Termination Intention Using EEG - Choi, Junhyuk; Lee, Song Joo; Kim, Seung Jong; Lee, Jong Min; Kim, Hyungmin (2018 6TH INTERNATIONAL CONFERENCE ON BRAIN-COMPUTER INTERFACE (BCI), 2018)
In this study, we employed a linear classifier to grasp the abstract features of electroencephalography (EEG) for recognizing voluntary gait intention and termination. We monitored Mu-band EEG to find gait intention and tried to detect a movement on/offset. Considerable gait-related (de) synchronization occurred hence, amplified by common spatial pattern (CSP). Performance of the classifier was evaluated in terms of classification success rates and false positive rates.